(untitled) (The Journal of Forensic Accounting Profession, 2022)
Forensic accounting as a profession plays a major role in preventing and detecting frauds and almost in all areas of business there is a need for the services of forensic accountants. In modern conditions, when the whole world is struggling with the COVID-19 pandemic and the consequences it brings, an increase in the number of frauds is expected, which will result in an increase of demand for specially trained experts in the area of fraud prevention and detection. In this context, this paper emphasizes the role of forensic accountant in the fight against fraud and presents the occupational standard and qualification standard developed for this profession in the Republic of Croatia. The occupational standard identifies key jobs within the profession as well as the competences that a person needs to possess to successfully perform jobs within the profession. (Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2021-0008, pod licencom CC BY-NC-ND 4.0)